Innovation under the radar : the nature and sources of innovation in Africa - Fu, Xiaolan, 1967- (Cambridge : Cambridge University Press, 2020)
Investigating the nature, drivers and sources of innovation in Africa, this book examines the channels for effective diffusion of innovation in and to Africa under institutional, resource and affordability constraints. Fu draws on almost a decade of research on innovation in Africa to explore these issues and unpack the process, combining a rigorous statistical analysis of a purposely designed multi-wave, multi-country survey with in-depth studies of representative cases. Building on this research, Fu argues that African firms are innovative but unsupported. Those 'under-the-radar' innovations that widely exist in Africa as a result of the constraints are not sufficient to enable Africa to leapfrog the innovation gap in the era of the fourth Industrial Revolution. This is the first comprehensive analysis of the creation and diffusion of innovation in low income countries. It also provides the first survey-based analysis of innovation in the informal economy.
Title from publisher's bibliographic system (viewed on 08 Dec 2020).
Keywords: Technological innovations -- Africa; Information technology -- Economic aspects -- Africa